2014
DOI: 10.1371/journal.pone.0094182
|View full text |Cite
|
Sign up to set email alerts
|

The S. pombe Translation Initiation Factor eIF4G Is Sumoylated and Associates with the SUMO Protease Ulp2

Abstract: SUMO is a small post-translational modifier, that is attached to lysine residues in target proteins. It acts by altering protein-protein interactions, protein localisation and protein activity. SUMO chains can also act as substrates for ubiquitination, resulting in proteasome-mediated degradation of the target protein. SUMO is removed from target proteins by one of a number of specific proteases. The processes of sumoylation and desumoylation have well documented roles in DNA metabolism and in the maintenance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 71 publications
(119 reference statements)
1
14
0
Order By: Relevance
“…The translation initiation factor eIF4F consists of three proteins: eIF4A, eIF4E and eIF4G. We and others have previously demonstrated that both mammalian eIF4E and eIF4G are sumoylated ( Xu et al, 2010 ; Jongjitwimol et al, 2014 ). We therefore wished to determine whether eIF4A is also modified by SUMO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The translation initiation factor eIF4F consists of three proteins: eIF4A, eIF4E and eIF4G. We and others have previously demonstrated that both mammalian eIF4E and eIF4G are sumoylated ( Xu et al, 2010 ; Jongjitwimol et al, 2014 ). We therefore wished to determine whether eIF4A is also modified by SUMO.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that fission yeast and mammalian eIF4G are sumoylated ( Jongjitwimol et al, 2014 ), and have identified two sumoylation sites in the C-terminus of human eIF4G. Our initial studies suggest that sumoylation might have a role in regulating protein synthesis in response to stress.…”
Section: Introductionmentioning
confidence: 85%
“…Both Ulp1 and Ulp2 desumoylate a subset of SUMO conjugates, with specificity likely driven in large part by their spatial separation (12). Ulp1 localizes to the nuclear rim by associating with nuclear pores, whereas Ulp2 is nucleoplasmic (12)(13)(14)(15)(16)(17)(18). In higher eukaryotes, SENP1/2 localize to nuclear pores like Ulp1 (19 -21), and SENP6/7, like Ulp2, are nucleoplasmic (22,23).…”
mentioning
confidence: 99%
“…Although not validated herein, we recently showed that as in other species fission yeast Top1 is a bona fide SUMO conjugate 37 . In addition, the translation initiation factor eIF4G was recently independently found to be SUMOylated 38 .…”
Section: Resultsmentioning
confidence: 99%